Syphilis in pregnancy and the problems facing congenital syphilis: An integrative review (Research, Society and Development, 2024)
The objective of this study is to analyze prenatal care and its associated factors in relation to Gestational Syphilis and Congenital Syphilis through an integrative literature review. Based on the combination of descriptors, 117 articles were found. After applying the inclusion and exclusion criteria, the final sample consisted of 08 articles. After analyzing and discussing them, we concluded that the factors associated with the increasing increase in Gestational Syphilis are mostly the deficiency of the Brazilian health system, inadequate prenatal care, treatment not performed or performed incorrectly, among others. The factors associated with Congenital Syphilis are inadequate case management, loss of opportunity for diagnosis and treatment, lack of family counseling, lack of treatment of the partner leading to reinfection, failure of prenatal care, maternal age under 20 years, low education, low income, and inadequate treatment. Therefore, prenatal care is the best tool for the early diagnosis of Syphilis in Pregnancy and subsequent treatment.